Implementation of Minister of Religious Affairs Regulation No. 20 of 2019 Concerning Taukil Wali Marriage - Siregar, Ganti; Siregar, Ramadhan Syahmedi (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2022)
Article 12 paragraph 5 of the Regulation of the Minister of Religion Number 20 of 2019 states that a guardian who is not present at the contract must make a letter taukil wali in front of the Head of the District Office of Religious Affairs/Penghulu/PPN LN according to domicile. This regulation creates a problem when a nasab guardian who cannot attend is replaced by a judge's guardian without a guardian's taukil letter, as happened in Kota Kisaran Barat. The purpose of this article is to find out the views of the Head of the Office of Religious Affairs in Kota Kisaran Barat Subdistrict regarding the taukil guardian of marriage in the Minister of Religion Regulation Number 20 of 2019, the application and impact of its implementation on household sustainability. This type of research is qualitative, with an empirical juridical approach. This article concludes that first: The Head of KUA Office of Kota Kisaran Barat District is of the view that if the nasab guardian cannot attend the marriage contract due to traveling, then the judge's guardian does the marriage. Second, the application of Minister of Religion Regulation Number 20 of 2019 concerning taukil wali in the Office of Religious Affairs in Kota Kisaran Barat District has been going well. Third, there is no negative impact that occurs after marriage through Taukil marriage guardian. This is because the taukil wali is not because the wali nasab does not agree, but because the circumstances and conditions of the wali nasab are far away and various other things that make them do taukil wali nikah